2017
DOI: 10.1007/s10459-017-9762-5
|View full text |Cite
|
Sign up to set email alerts
|

Participation and selection effects of a voluntary selection process

Abstract: Many different medical school selection processes are used worldwide. In this paper, we examine the effect of (1) participation, and (2) selection in a voluntary selection process on study performance. We included data from two cohorts of medical students admitted to Erasmus MC, Rotterdam and VUmc, Amsterdam, The Netherlands and compared them to previously published data from Groningen medical school, The Netherlands. All included students were admitted based on either (1) a top pre-university grade point aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Apparently, in predicting academic performance, participation in a time‐consuming voluntary selection procedure is more important than acceptance . Unfortunately, the earlier reported participation effects with respect to study delay and lower grades were not consistently confirmed in a follow‐up multi‐site study . Hence, the conclusion was that participation effects seem to be mediated by institutional differences in curricula and in selection procedures …”
Section: Non‐grades‐based Selection In the Netherlandsmentioning
confidence: 92%
See 2 more Smart Citations
“…Apparently, in predicting academic performance, participation in a time‐consuming voluntary selection procedure is more important than acceptance . Unfortunately, the earlier reported participation effects with respect to study delay and lower grades were not consistently confirmed in a follow‐up multi‐site study . Hence, the conclusion was that participation effects seem to be mediated by institutional differences in curricula and in selection procedures …”
Section: Non‐grades‐based Selection In the Netherlandsmentioning
confidence: 92%
“…31,33,37 Unfortunately, the earlier reported participation effects with respect to study delay and lower grades were not consistently confirmed in a follow-up multi-site study. 38 Hence, the conclusion was that participation effects seem to be mediated by institutional differences in curricula and in selection procedures. 38 Assessing pre-university extracurricular activities Several Dutch medical schools, including our own, have operationalised non-academic skills by examining applicants' extracurricular activities during pre-university education (puECAs).…”
Section: A Participation Effect?mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research studying the three admission groups in this setting has yielded inconsistent findings. Top GPA students consistently outperform other students in academic and non-academic performance outcomes [3,4,[7][8][9][10], while comparisons between selected students and lotteryadmitted students on various study performance outcomes yield either no statistically significant differences or show that selected students perform significantly better than lottery-admitted students [3,4,[8][9][10][11][12][13][14][15]. A Danish study also found that students who were admitted based on a qualitative selection procedure outperformed students admitted based only on their pu-GPA [16].…”
Section: Introductionmentioning
confidence: 99%
“…Year-1 performance / course credits GPA: No differences (Hulsman et al, 2007;Wouters et al, 2017b) for 3 out of 4 cohorts (Urlings-Strop et al, 2009;Lucieer et al, 2015) Selected > lottery-admitted (Schripsema et al, 2014;Schripsema et al, 2017;Schreurs et al, 2018b), including rejected lottery-admitted (de Visser et al, 2017); for 1 out of 4 cohorts in 1 out of 4 study years (Urlings-Strop et al, 2009) Progress test: Selected > rejected lottery-admitted (Schreurs et al, 2018b) OSCE: percentage fail (/non-fail): no differences (Schreurs et al, 2018b) percentage good (/non-good): selected > rejected lottery-admitted (Schreurs et al, 2018b) Course credits: No differences (Hulsman et al, 2007;Urlings-Strop et al, 2009;Wouters et al, 2017b); no differences between selected and rejected lottery-admitted (de Visser et al, 2017;Schripsema et al, 2017) Selected and rejected lottery-admitted > lottery-admitted (Schripsema et al, (2014)(de Visser et al, 2017 Selected > rejected lottery-admitted (Schripsema et al, 2017) Selected > lottery (after including early medical school performance this did not remain) Year-2 performance / course credits GPA: No differences between selected and rejected lottery-admitted (Schreurs et al, 2018b) Progress test: Selected > rejected lottery-admitted (Schreurs et al, 2018b) OSCE: percentage fail (/non-fail): no differences (Schreurs et al, 2018b) percentage good (/non-good): selected > rejected lottery-admitted (Schreurs et al, 2018b) Course credits: No differences between selected and lottery-admitted (de Visser et al, 2017) Selected and rejected lottery-admitted > lottery-admitted (Schripsema et al, 2014) Selected > rejected lottery-admitted (de Visser et al, 2017) Year-3 performance / course credits Cognitive tests: Critical Appraisal of a Topic test: no differences for (Schreurs et al, 2018b) Percentage fail...…”
Section: Resultsmentioning
confidence: 99%